How cool is to be engaged with Drunk Elephant? An analysis of usergenerated content campaigns on Instagram - Bilro, R. G. (2022)
This study aims to understand the effect of user-generated content (UGC) campaigns on consumers’ perceptions of brand coolness and its influence on consumer brand engagement. The trendy concept of coolness in the beauty industry is studied through UGC, assessing if brands encouraging consumers to post about their experiences leads to consumers perceiving brands as cool and creating a deeper sense of engagement with that brand. This research intends to assess the interactions incited by a UGC campaign led by the prestigious beauty brand Drunk Elephant. Researchers employed a netnography methodology followed by a sentiment analysis technique to conduct that analysis. Data was retrieved from Instagram for one year using a text-mining tool capable of extracting the comments (67,321 interactions) and analysed using Natural Language Processing tools. Results confirm that adopting UGC campaigns can lead to consumers perceiving a brand to be cool and positively influencing consumer brand engagement.